BRANDING AND PERSONAL BRANDING IN THE SOCIAL MEDIA ERA - Silvia Ekasari (ADISAM PUBLISHER, 2025)
In the social media era, branding and personal branding have become vital elements in building a strong image and presence. Social media offers the opportunity to reach a wide audience and engage with them directly, enabling brands and individuals to strengthen their influence. Relationships built through transparent and responsive interactions increase trust and loyalty. Therefore, an effective branding strategy on social media is essential to increase recognition, strengthen relationships with audiences, and open up growth opportunities for both businesses and individuals